Focused Classroom Coaching and Widespread Racial Equity in School Discipline - Anne Gregory; Erik A. Ruzek; Jamie DeCoster; Amori Yee Mikami; Joseph P. Allen (SAGE Publishing, 2019)
We examined the effects of a teacher coaching program on discipline referrals using records from 7,794 U.S. classrooms in secondary schools. Some classroom teachers took part in a trial: They were randomized to receive intensive coaching in a focal classroom or to form a business-as-usual control group. The remaining teachers taught in the same schools as the teachers in the trial. Previous research suggested that the coaching program was associated with increasing equity in discipline referrals in focal, coached classrooms. The current study addressed whether effects found in the teachers' focal, coached classrooms generalized to diverse classrooms in their course load. Results suggested that the coaching program had no generalized effects on reducing referrals with African American students or racial referral gaps in classrooms with coached teachers, relative to the control teachers and the other teachers in the schools. We offer implications for coaching programs and directions for equity-oriented efforts to reduce racial discipline gaps.